2007
DOI: 10.1001/archopht.125.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Microbial Keratitis in Taiwanese Children

Abstract: To study the clinical and microbiological characteristics of pediatric microbial keratitis in Taiwan. Methods: The medical records of 81 eyes with microbial keratitis in 78 children aged 16 years or younger who were diagnosed and treated at Chang Gung Memorial Hospital, Taipei, Taiwan, from July 1, 1998, through December 31, 2002, were retrospectively reviewed. Predisposing factors, microbial culture results, clinical course, and visual outcomes were analyzed. Results: Predisposing factors were contact lens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
68
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 24 publications
14
68
5
Order By: Relevance
“…Previous studies showed that 11.8-39.3% of childhood microbial keratitis, not just bacterial infection, had a visual outcome of worse than 6/60. 2,7,8,24 Variations in the reported visual impairment rate may be because of the inclusion of patients with different severity and different pathogen. Relationships between the presence of visual impairment and clinical characteristics of paediatric patients were also explored in the present study, and Gram-negative bacterial infection and the increasing number of resistant antibiotics were found to be independent risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that 11.8-39.3% of childhood microbial keratitis, not just bacterial infection, had a visual outcome of worse than 6/60. 2,7,8,24 Variations in the reported visual impairment rate may be because of the inclusion of patients with different severity and different pathogen. Relationships between the presence of visual impairment and clinical characteristics of paediatric patients were also explored in the present study, and Gram-negative bacterial infection and the increasing number of resistant antibiotics were found to be independent risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few studies from the United States, India, and Taiwan have demonstrated its characteristics, 1,[4][5][6][7][8] with predisposing factors reported to be contact lens wear, trauma, ocular disease, systemic disease, and environmental factors. 2,9,10 The purpose of this study was to review the microbiological profile and in vitro antibiotic susceptibility of paediatric bacterial keratitis diagnosed by our institution, and to explore their relationships with visual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…18 In one of the largest pediatric specific series of microbial keratitis, only 2 patients out of 78 presented with perforation. 30 Other techniques described to treat corneal perforations include LK or DLK, PKP with glycerin cryopreserved grafts and most recently crosslinking. 24,25,[31][32][33] All these have limited experience in children.…”
Section: Discussionmentioning
confidence: 99%
“…Other signs are redness of the eye, blepharitis lid edema, satellite lesions, increasing eye pain, or discomfort or foreign body sensation, increased light sensitivity, raised slough, dry eyes, abnormalities and conjunctival congestion, corneal degeneration, and defective vision (4). In children, corneal ulcers, as defined by the corneal infiltrate, hypopyon, and perforations were reported with no significant difference between age groups (16). If 1 or 3 clinical features (raised slough, dry eyes, abnormalities, conjunctival congestion, corneal degeneration and defective vision pain, serrated margins, raised slough, hypopyon, redness of the eye, blepharitis lid edema, and fibrinous exudates) were present, the probabilities of FK would have been 63% and 83%, respectively (22).The most infected site is cornea (23).…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…If 1 or 3 clinical features (raised slough, dry eyes, abnormalities, conjunctival congestion, corneal degeneration and defective vision pain, serrated margins, raised slough, hypopyon, redness of the eye, blepharitis lid edema, and fibrinous exudates) were present, the probabilities of FK would have been 63% and 83%, respectively (22).The most infected site is cornea (23). Infection was reported the most with male preponderance, with a male-to-female ratio of 147/234, 62.8% (3), but there was a report indicating no significant difference in sex (16). Infection frequently occurs in males in agricultural activities, especially during summer, and if children do not use any protection for the eyes, they become infected by the plant debris, leaf spots, vegetative garbage, seedling blight, and seed germination.…”
Section: Signs and Symptomsmentioning
confidence: 99%